TRIM8-associated non-coding RNA panel as a biomarker for Lupus nephritis activity - Elgawad, Mostafa Abdelnasier Abd; Shinnawy, Howayda Abdelhamid El; Eissa, Sanaa; Ali, Nouran Abdelfattah Sayed; Behairy, Maha Abdelmoneim; Kamel, Cherry Reda; Kamel, Marwa Mostafa (Journal of translational medicine, 2025)
Background Lupus nephritis (LN) represents a major complication in systemic lupus erythematosus (SLE). The objective of this study was to evaluate the TRIM8 gene and its associated non-coding RNAs ( lnc-SSBP2-1:1 and hsa-miR-126-5p ) as potential non-invasive biomarkers for LN activity. Methods Bioinformatics analyses were initially employed to identify candidate mRNA and associated non-coding RNAs (ncRNAs) implicated in LN. Expression profiles of TRIM8lnc-SSBP2-1:1 and hsa-miR-126-5p were validated in blood samples from 40 active LN, 30 inactive LN patients, and 20 healthy individuals via real-time PCR. Results TRIM8 mRNA and lnc-SSBP2-1:1 lncRNA levels were notably upregulated in active LN ( p < 0.001), while hsa-miR-126-5p was reduced ( p < 0.001). SLEDAI-2K scores correlated positively with TRIM8 mRNA and lnc-SSBP2-1:1 , and negatively with hsa-miR-126-5p . Conclusions This study highlights TRIM8 -associated ncRNA regulatory network as promising biomarkers in LN activωity, with potential clinical impact. Graphical abstract Highlights TRIM8 and lnc-SSBP2-1:1 are upregulated, hsa-miR-126-5p is downregulated in active LN Biomarkers strongly correlated with SLEDAI-2K disease activity scores High diagnostic accuracy (AUCs > 0.93) in distinguishing active vs inactive LN Potential non-invasive tool to complement current LN monitoring